The Genetic and Imaging Key to Understanding Bicuspid Aortic Valve Disease - Vaneeza Moosa; Julio Garcia (Applied Sciences)
Bicuspid Aortic Valve (BAV) is a prevalent congenital heart defect, characterized by the presence of two cusps instead of three, leading to significant clinical implications such as aortic stenosis, regurgitation, and aneurysms. Understanding the genetic underpinnings of BAV is essential for early diagnosis and management, which can prevent severe complications like aortic dissection and heart failure. Recent studies have identified critical genes associated with BAV, including NOTCH1, GATA4, GATA5, SMAD6, NKX2.5, BMP2, and ROBO4, all of which play vital roles in aortic valve development and function. Imaging advancements, particularly in cardiac MRI and echocardiography, have enhanced the assessment of valve morphology and hemodynamics, with Wall Shear Stress emerging as a promising biomarker. This review consolidates current genetic and imaging research, elucidating the contributions of genetic variants to the etiology and progression of BAV, while emphasizing the importance of imaging biomarkers in clinical management. The findings aim to improve genetic screening strategies, facilitate early diagnosis, and guide the development of targeted therapies for individuals with BAV.